The Boma: Phages - Bad for bacteria, good for livestock farmers - International Livestock Research Institute (International Livestock Research Institute, 2021)
Livestock farmers use antibiotics to treat infections in their animals, and may also use them as a preventative. But overuse of antibiotics can create 'superbugs' - antimicrobial-resistant (AMR) bacteria which threaten human lives and wellbeing, as well as those of livestock animals. Presenters Brenda Coromina and Elliot Carleton explore one approach that ILRI scientists are taking to combat the AMR problem - phages. These 'bacteria-eating' viruses, which naturally exist in the environment, are being studied by ILRI scientists to develop an alternative treatment to antibiotics. They hear from 'phage hunters' Angela Makumi and Nicholas Svitek about how phages work, what makes them different from antibiotics, and what it will take to make phage therapy a reality. Could phages become our future weapon of choice against bacteria?